The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/codi.15372
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with healing, reoperation and continence disturbance in patients following surgery for fistula‐in‐ano

Abstract: Aim Fistula-in-ano (FIA) is associated with high treatment costs and has a deleterious impact on quality of life. A wide range of healing, incontinence and recurrence rates have been reported. This study aimed to identify operative, patient and disease factors that influence these outcomes after surgery for FIA. Method An observational cohort study of consecutive patients who were managed for FIA at a tertiary colorectal practice (1999-2019) was performed. Outcome measures included healing, impaired continence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…43 Unfortunately, compared to patients undergoing repair of cryptoglandular anal fistulas, patients with CD-associated perianal disease have lower rates of initial and definitive closure as well as a higher risk of requiring multiple repair procedures. 44 Still, multiple studies, including at least one randomized trial, have demonstrated that the addition of surgical closure to baseline medical therapy improves long-term healing rates and decreases the risk of future procedural intervention. 45 For all repair procedures, the general goal remains the same: improvement if not resolution of fistula symptoms without altering or impairing fecal continence.…”
Section: Pathogenesis Classification and Initial Evaluationmentioning
confidence: 99%
“…43 Unfortunately, compared to patients undergoing repair of cryptoglandular anal fistulas, patients with CD-associated perianal disease have lower rates of initial and definitive closure as well as a higher risk of requiring multiple repair procedures. 44 Still, multiple studies, including at least one randomized trial, have demonstrated that the addition of surgical closure to baseline medical therapy improves long-term healing rates and decreases the risk of future procedural intervention. 45 For all repair procedures, the general goal remains the same: improvement if not resolution of fistula symptoms without altering or impairing fecal continence.…”
Section: Pathogenesis Classification and Initial Evaluationmentioning
confidence: 99%
“…This has led to the development of new strategies to improve current techniques. 2 Historically, seton placement was the main method of surgical management for most perianal fistulas. Setons allow the drainage of associated abscesses while promoting the resolution of the tract through a local inflammatory process.…”
Section: Introductionmentioning
confidence: 99%